2022
DOI: 10.1093/infdis/jiac178
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Neutralizing Activity Against Omicron Could Be Obtained in SARS-CoV-2 Convalescent Patients Who Received Two Doses of mRNA Vaccination

Abstract: The SARS-CoV-2 variant Omicron is now under investigation. We evaluated cross-neutralizing activity against Omicron in COVID-19 convalescent patients (n = 23) who had received two doses of an mRNA vaccination (BNT162b2 or mRNA-1273). Intriguingly, after the second vaccination, the neutralizing antibody titers of subjects against SARS-CoV-2 variants, including Omicron, all became seropositive, and significant fold-increases (21.1–52.0) were seen regardless of the disease severity of subjects. Our findings thus … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 10 publications
3
18
0
Order By: Relevance
“…Other groups could show that the T‐cell and antibody responses against SARS‐CoV‐2 spike glycoprotein remain effective against the currently dominating B.1.1.529 VoC 45,87–90 . We support these observations in this high‐resolution analysis.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Other groups could show that the T‐cell and antibody responses against SARS‐CoV‐2 spike glycoprotein remain effective against the currently dominating B.1.1.529 VoC 45,87–90 . We support these observations in this high‐resolution analysis.…”
Section: Discussionsupporting
confidence: 83%
“…Other groups could show that the T‐cell and antibody responses against SARS‐CoV‐2 spike glycoprotein remain effective against the currently dominating B.1.1.529 VoC. 45 , 87 , 88 , 89 , 90 We support these observations in this high‐resolution analysis. We found that every individual in our study still had at least seven CD4 + T‐cell specificities that were conserved in all VoCs and LUMs investigated.…”
Section: Discussionsupporting
confidence: 76%
“…To isolate mAbs targeting common epitopes of SARS-CoV-2 variants, we searched for antibody genes from PBMCs of infected and subsequently vaccinated patients. We selected three PBMCs from the patients who showed high neutralizing activity against all of the D614G, Delta, and Omicron BA.1 variants previously we reported (Kurahashi et al, 2022a). In the single B cells isolated from the PBMCs, ten antibody genes were further selected based on the ELISA findings of Fabs produced by the Ecobody technology (Ojima-Kato et al, 2017), and we tested the purified recombinant IgG antibodies with the V genes.…”
Section: Resultsmentioning
confidence: 99%
“…MO1 is derived from PBMCs of individuals who were infected with a SARS-CoV-2 variant□—□presumably the wildtype with only the D614G mutation in the spike□—□and then received two doses of an mRNA vaccine encoding the spike gene of the ancestral SARS-CoV-2 (Kurahashi et al, 2022a). Our finding that MO1 can broadly neutralize the early SARS-CoV-2 variants and the Omicron BA.1, BA.1.1, BA.2 and BA.5 variants demonstrates that immunity against the spike with the ancestral SARS-CoV-2 RBD sequence can protect humans by inducing neutralizing antibodies, like MO1, that recognize conserved epitopes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation